The Teachers’ Effective English Listening Comprehension Strategies for Senior High School Students - Rahayu, Arum Putri (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2024)
The purpose of this study was to find out how teachers at MA Ma'arif Jogorogo applied strategies to teach aspects of listening. The teachers were selected through purposive sampling, which involved the selection of samples based on specific criteria. Based on the purposive sampling method, two teachers were selected as research samples. A qualitative descriptive research approach was used to examine three aspects of teachers' strategies: their interpretation of teaching strategies, their actual teaching methods, and their assessment of students' listening comprehension. Data collection involved semi-structured interviews to gain in-depth insights from the respondents. Data analysis used interactive analysis models from Miles and Huberman. The research revealed that teachers' interpretations of strategies were closely interrelated with other skills, impacting learning outcomes significantly. Additionally, the use of different strategies facilitated students to more easily understand the material discussed. Furthermore, the use of different strategies could lead to varying results. Moreover, the use of audio-visual media allowed students to directly hear the sound and focus on the content in question, followed by group discussions and quizzes that encouraged direct and spontaneous student responses. Finally, teachers assessed students' work through various exercises, such as summarizing the material, identifying main ideas, making presentations, and engaging in question and answer sessions. _________________________________________________________________________________________ Tujuan dari penelitian ini adalah untuk mengetahui bagaimana guru di MA Ma'arif Jogorogo menerapkan strategi untuk mengajar aspek mendengarkan. Para guru dipilih melalui cara purposive sampling, yaitu pemilihan sampel dengan kriteria-kriteria yang telah disebutkan. Berdasarkan metode purposive sampling tersebut didapatkan dua orang guru sebagai sampel penelitian. Pendekatan penelitian deskriptif kualitatif digunakan untuk menguji tiga aspek strategi guru: interpretasi mereka terhadap strategi pengajaran, metode pengajaran mereka yang sebenarnya, dan penilaian mereka terhadap pemahaman mendengarkan siswa. Pengumpulan data melibatkan wawancara semi-terstruktur untuk mendapatkan wawasan mendalam dari para responden. Analisis data menggunakan model analisis interaktif dari Miles and Huberman. Penelitian ini mengungkapkan bahwa interpretasi guru terhadap strategi saling terkait erat dengan keterampilan lain, berdampak pada hasil pembelajaran secara signifikan. Selain itu, penggunaan strategi yangnberbeda juga memfasilitasi para siswa agar lebih mudah dalam memahami materi yang didiskusikan. Selain itu, penggunaan strategi yang berbeda dapat menyebabkan hasil yang bervariasi. Selanjutnya, penggunaan media audio visual memungkinkan siswa untuk langsung mendengar suara dan fokus pada konten yang dimaksud, diikuti dengan diskusi kelompok dan kuis yang mendorong tanggapan siswa secara langsung dan spontan. Akhirnya, guru menilai pekerjaan siswa melalui berbagai latihan, seperti meringkas materi, mengidentifikasi ide-ide utama, melakukan presentasi, dan terlibat dalam sesi tanya jawab